2008
DOI: 10.1093/humrep/den050
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian hormone indicates early ovarian decline in fragile X mental retardation (FMR1) premutation carriers: a preliminary study

Abstract: These preliminary data suggest that AMH levels indicate early ovarian decline among women with longer FMR1 repeat alleles; moreover, AMH appears to be a better marker than FSH in identifying this early decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 35 publications
1
59
0
1
Order By: Relevance
“…More recent studies have shown reduced levels of AMH among premutation carriers compared with non-carriers, again, consistent with an aging ovary (121).…”
Section: Non-syndromic Poimentioning
confidence: 64%
“…More recent studies have shown reduced levels of AMH among premutation carriers compared with non-carriers, again, consistent with an aging ovary (121).…”
Section: Non-syndromic Poimentioning
confidence: 64%
“…Although some studies showed evidence of earlier age of onset of FXPOI and higher penetrance of mid-range premutations of 80 -100 repeats, 24,25 we chose to use the definition of higher risk alleles of Ն70 repeats in our calculation as defined by Rohr et al 22 We choose to use Ն70 repeats in our calculations for FXTAS and FXPOI for consistency in defining larger premutation alleles and because several studies examined penetrance of larger premutation alleles in FXTAS and FXPOI. 16,17,22 …”
Section: Discussionmentioning
confidence: 99%
“…Female premutation carriers show overall higher levels of follicular stimulating hormone than do normal or full mutation carriers, along with decreased levels of anti-Müllerian hormone, Inhibin A, and Inhibin B-all indicators of ovarian decline. 19,21,22 All women who are premutation carriers will have an increased risk of suffering from FXPOI, 22,23 with evidence of earlier onset of FXPOI in female carriers of mid premutations range of 80 -100 repeats than carriers of shorter or longer premutation alleles. 24,25 Penetrance of FXPOI seems to be higher in carriers of mid premutation alleles (18.6%), when compared with lower or longer premutation carriers, 5.9% and 12.5%, respectively.…”
mentioning
confidence: 99%
“…Notwithstanding the extensive number of scientific papers in the last few years, no definitive consensus exists on the characterization of altered ovarian function [29]. A combination of hormonal markers like serum follicle-stimulating hormone (FSH) [52], serum AMH [79] and the antral follicle count [77] may help in diagnosing early decline in ovarian follicular activity. The antral follicle count remains perhaps the best predictor of the ovarian response to the controlled ovarian stimulation after the AMH assay itself [80,88] Although early follicular phase serum FSH levels are a well established marker of ovarian reserve [18], the correlation may be poor compared to other markers.…”
Section: Cgg Mutations and Biomarkers Of Ovarian Reservementioning
confidence: 99%